Combating the COVID-19 pandemic in a resource-constrained setting: insights from initial response in India. Issue 11 (13th November 2020) - ,
Abstract : The low-and-middle-income country (LMIC) context is volatile, uncertain and resource-constrained. India, an LMIC, has put up a complex response to the COVID-19 pandemic. Using an analytic approach, we have described India's response to combat the pandemic during the initial months (from 17 January to 20 April 2020). India issued travel advisories and implemented graded international border controls between January and March 2020. By early March, cases started to surge. States scaled up movement restrictions. On 25 March, India went into a nationwide lockdown to ramp up preparedness. The lockdown uncovered contextual vulnerabilities and stimulated countermeasures. India leveraged existing legal frameworks, institutional mechanisms and administrative provisions to respond to the pandemic. Nevertheless, the cross-sectoral impact of the initial combat was intense and is potentially long-lasting. The country could have further benefited from evidence-based policy and planning attuned to local needs and vulnerabilities. Experience from India offers insights to nations, especially LMICs, on the need to have contextualised pandemic response plans.